Wildwood Creek [large type] - Wingate, Lisa (Center Point Large Print, 2014)
While working as a costuming assistant on a docudrama, Allie Kirkland has discovered strange connections between herself and a teacher who disappeared a century ago in the legendary frontier settlement of Wildwood. Is history about to repeat itself?